2010
DOI: 10.1152/ajprenal.00581.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain stimulates Na-K-ATPase through a sodium/hydrogen exchanger-1 (NHE-1)-dependent mechanism in human kidney proximal tubule cells

Abstract: Recent investigations demonstrate increased Na/H exchanger-1 (NHE-1) activity and plasma levels of ouabain-like factor in spontaneously hypertensive rats. At nanomolar concentrations, ouabain increases Na-K-ATPase activity, induces cell proliferation, and activates complex signaling cascades. We hypothesize that the activity of NHE-1 and Na-K-ATPase are interdependent. To test whether treatment with picomolar ouabain regulates Na-K-ATPase through an NHE-1-dependent mechanism, we examined the role of NHE-1 in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 62 publications
2
59
1
Order By: Relevance
“…Recent studies from our laboratory have demonstrated that treatment with low-dose ouabain, concentrations similar to those present in ESRD patients, increases blood pressure in rats and increases Na C /K C ATPase activity in basolateral membranes prepared from kidney cortex. The increase in activity was dependent upon the presence of NHE1 (SLC9A1) expression and was inhibited by specific inhibitors of NHE1 (Holthouser et al 2010). We also demonstrated that low-dose cardiotonic steroids increase the association between Na C /K C ATPase and NHE1 and that this association is critical for activation of the Src-EGFR signaling cascade.…”
Section: Atpase Activitymentioning
confidence: 60%
See 1 more Smart Citation
“…Recent studies from our laboratory have demonstrated that treatment with low-dose ouabain, concentrations similar to those present in ESRD patients, increases blood pressure in rats and increases Na C /K C ATPase activity in basolateral membranes prepared from kidney cortex. The increase in activity was dependent upon the presence of NHE1 (SLC9A1) expression and was inhibited by specific inhibitors of NHE1 (Holthouser et al 2010). We also demonstrated that low-dose cardiotonic steroids increase the association between Na C /K C ATPase and NHE1 and that this association is critical for activation of the Src-EGFR signaling cascade.…”
Section: Atpase Activitymentioning
confidence: 60%
“…Therefore, it remains to be determined whether different Na C /K C ATPase isoforms play such different roles in cardiotonic steroid-mediated blood pressure development in humans. This review highlights recent exciting studies investigating the effects of physiological and pathophysiological concentrations of cardiotonic steroids on renal salt reabsorption (Aizman et al 2001, Abramowitz et al 2003, Aizman & Aperia 2003, Contreras et al 2006, Khundmiri et al 2006, Aperia 2007, Nguyen et al 2007, Holthouser et al 2010, Jansson et al 2012, Bignami et al 2013, Blanco & Wallace 2013). …”
Section: Introductionmentioning
confidence: 97%
“…Ouabain also enhances LPS-down-regulated inducible nitric-oxide synthase activity in peritoneal macrophages (51). Interestingly, at low concentrations (nanomolar and picomolar), ouabain stimulates Na ϩ /K ϩ -ATPase activity (28) and activates complex signaling cascades in kidney cells (30). In subnanomolar concentrations, ouabain stimulates proliferation and differentiation of cardiac and smooth muscle cells (52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ability of NHE1 to contribute to adaptive regulation in renal tubules may take on broader significance as additional functions for NHE1 in vectorial transport are recognized. For example, recent studies suggest that NHE1 can interact with the Na ϩ -K ϩ -ATPase ␣-subunit to modulate sodium pump activity in proximal tubule cell lines (37). Last, our studies provide a basis for future investigations into other physiological conditions and disease states that may alter renal tubule functions through adaptations in NHE1.…”
Section: Of Hcomentioning
confidence: 66%